Privacy, People, and Markets. Issue 4 (2019) - Hull, Gordon
Abstract: Most current work on privacy understands it according to an economic model: individuals trade personal information for access to desired services and websites. This sounds good in theory. In practice, it has meant that online access to almost anything requires handing over vast amounts of personal information to the service provider with little control over what happens to it next. The two books considered in this essay both work against that economic model. In Privacy as Trust, Ari Ezra Waldman argues for a new model of privacy that starts not with putatively autonomous individuals but with an awareness that managing information flows is part of how people create and navigate social boundaries with one another. Jennifer Rothman's Right of Publicity confronts the explosive growth of publicity rights—the rights of individuals to control and profit from commercial use of their name and public image—and, in so doing, she exposes the poverty of treating information disclosure merely as a matter of economic calculation. Both books emphasize practical and doctrinal solutions to the problems they identify. In this essay, I take a step back and draw out the extent to which they converge on a fundamentally important point: the blunt application of market logic with its tools of property and contracts fails to protect the interests that lead us to turn to privacy in the first place; the tendency to economize privacy is a significant part of why we inadequately protect it.